BEST PRACTICES OF CHURCH BUILDING BASED ON LOCAL WISDOM IN KENDARI CITY: A STUDY IN THE STASI ANDUONOHU OF CATHOLIC CHURCH - Muhammad Ali Saputra (Al-Qalam, 2021)
Although the Constitution has guaranteed the construction of places of worship in several areas, especially in the context of majority-minorities, it still faces many obstacles. The government issued PBM regulations No. 9 and 8 of 2006 to solve the problem of building houses of worship administratively, but often, in the conflict cases over the construction of places of worship, it does not provide the expected solution. This study tries to look at local wisdom as an alternative capital for best practice in constructing houses of worship in Kendari City. By taking the construction of the Anduonohu Stasi of Catholic Church as a case, the researchers found that the construction of the Anduonohu Stasi of Catholic Church proceeded peacefully. The church could fulfill the administrative requirements according to applicable regulations, without rejection from residents who were predominantly Muslim. In the construction of the church, although it is not explicitly said to be based on local wisdom, the construction of the Anduonohu Stasi of Catholic Church is supported by values/sense of responsibility, mutual respect, and love, as well as a willingness to sacrifice as shown by the residents around the church and other parties, and the church itself. The community around the church did not participate in providing financial or labor assistance. However, their willingness to accept a different place of worship in their environment by not making efforts to reject it. Meanwhile, from the government side, participation takes the form of granting permits, recommendations, and distributing aid. The limited-time in data collection requires further exploration regarding the best practice for the church's construction and the local wisdom of the residents around the environment.